Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve for [tex]\( k \)[/tex] such that the polynomial [tex]\( 3x^2 - 11x + k \)[/tex] is a perfect square, we will follow the logic that a perfect square trinomial can be expressed in the form [tex]\((ax + b)^2\)[/tex].
1. Assume the Polynomial is a Perfect Square:
If [tex]\( 3x^2 - 11x + k \)[/tex] is a perfect square, it should be expressible as [tex]\((ax + b)^2\)[/tex].
2. Expand the Perfect Square:
Expanding [tex]\((ax + b)^2\)[/tex], we get:
[tex]\[ (ax + b)^2 = a^2x^2 + 2abx + b^2 \][/tex]
3. Match Coefficients with the Given Polynomial:
Compare this expanded form with the polynomial [tex]\( 3x^2 - 11x + k \)[/tex]:
[tex]\[ 3x^2 - 11x + k = a^2x^2 + 2abx + b^2 \][/tex]
4. Determine [tex]\( a \)[/tex]:
From the coefficient of [tex]\( x^2 \)[/tex], we have:
[tex]\[ a^2 = 3 \][/tex]
Solving for [tex]\( a \)[/tex], we get:
[tex]\[ a = \sqrt{3} \quad \text{or} \quad a = -\sqrt{3} \][/tex]
5. Determine [tex]\( b \)[/tex]:
From the coefficient of [tex]\( x \)[/tex], we have:
[tex]\[ 2ab = -11 \][/tex]
Substituting [tex]\( a = \sqrt{3} \)[/tex], we solve for [tex]\( b \)[/tex]:
[tex]\[ 2\sqrt{3}b = -11 \quad \Rightarrow \quad b = \frac{-11}{2\sqrt{3}} = -\frac{11\sqrt{3}}{6} \][/tex]
6. Determine [tex]\( k \)[/tex]:
From the constant term, [tex]\( b^2 \)[/tex], we have:
[tex]\[ k = b^2 \][/tex]
Substituting the value of [tex]\( b \)[/tex]:
[tex]\[ b = -\frac{11\sqrt{3}}{6} \][/tex]
Therefore:
[tex]\[ k = \left( -\frac{11\sqrt{3}}{6} \right)^2 = \frac{121 \cdot 3}{36} = \frac{363}{36} = \frac{121}{12} \][/tex]
To summarize, the value of [tex]\( k \)[/tex] that makes the polynomial [tex]\( 3x^2 - 11x + k \)[/tex] a perfect square is:
[tex]\[ k = \frac{121}{12} \][/tex]
1. Assume the Polynomial is a Perfect Square:
If [tex]\( 3x^2 - 11x + k \)[/tex] is a perfect square, it should be expressible as [tex]\((ax + b)^2\)[/tex].
2. Expand the Perfect Square:
Expanding [tex]\((ax + b)^2\)[/tex], we get:
[tex]\[ (ax + b)^2 = a^2x^2 + 2abx + b^2 \][/tex]
3. Match Coefficients with the Given Polynomial:
Compare this expanded form with the polynomial [tex]\( 3x^2 - 11x + k \)[/tex]:
[tex]\[ 3x^2 - 11x + k = a^2x^2 + 2abx + b^2 \][/tex]
4. Determine [tex]\( a \)[/tex]:
From the coefficient of [tex]\( x^2 \)[/tex], we have:
[tex]\[ a^2 = 3 \][/tex]
Solving for [tex]\( a \)[/tex], we get:
[tex]\[ a = \sqrt{3} \quad \text{or} \quad a = -\sqrt{3} \][/tex]
5. Determine [tex]\( b \)[/tex]:
From the coefficient of [tex]\( x \)[/tex], we have:
[tex]\[ 2ab = -11 \][/tex]
Substituting [tex]\( a = \sqrt{3} \)[/tex], we solve for [tex]\( b \)[/tex]:
[tex]\[ 2\sqrt{3}b = -11 \quad \Rightarrow \quad b = \frac{-11}{2\sqrt{3}} = -\frac{11\sqrt{3}}{6} \][/tex]
6. Determine [tex]\( k \)[/tex]:
From the constant term, [tex]\( b^2 \)[/tex], we have:
[tex]\[ k = b^2 \][/tex]
Substituting the value of [tex]\( b \)[/tex]:
[tex]\[ b = -\frac{11\sqrt{3}}{6} \][/tex]
Therefore:
[tex]\[ k = \left( -\frac{11\sqrt{3}}{6} \right)^2 = \frac{121 \cdot 3}{36} = \frac{363}{36} = \frac{121}{12} \][/tex]
To summarize, the value of [tex]\( k \)[/tex] that makes the polynomial [tex]\( 3x^2 - 11x + k \)[/tex] a perfect square is:
[tex]\[ k = \frac{121}{12} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.